LEADERSHIP CHALLENGES OF REGIONAL BANKS IN INDONESIA - Roberto Akyuwen; Caroline Mangowal (KINERJA, 2019)
Bank Pembangunan Daerah (BPD) or the Regional Development Bank of Indonesia is designed to be an agent for regional development with products and services that contribute to the improvement of employment, poverty, disparity, financial literacy and inclusion. However, regional government leaders often intervene with operations and decision making in the banks. To study the extent to which external factors influence leadership in the BPD, this qualitative study used secondary data from the Financial Service Authority or Otoritas Jasa Keuangan (OJK) combined with interviews with BPD leaders and stakeholders. The findings show that the interventions of the regional government leaders were highly influential and resulted in negative consequences on BPD management which directly or indirectly affected the performance of the banks. This study is expected to provide insights into measures which would promote the role of regional banks as a development agent. Keywords: development agent, interventions, leaderships, Regional Development Banks